VALIDITY AND INTRA-RATER RELIABILITY OF LASER GONIOMETER VERSUS ELECTRO-GONIOMETER IN MEASURING SHOULDER RANGE OF MOTION (International Journal of Physiotherapy, 2019)
Background: Providing new objective valid and reliable methods of assessment of a range of motion is always a persistent need for clinical practitioners and researchers in physical therapy for obtaining précised and realistic diagnostic and treatment decisions. So this study was carried out to test the validity and intra-rater reliability of the laser goniometer via comparing repeated measures of laser and electro-goniometers in measuring a range of motion of shoulder movements considering the electro-goniometer as the reference standard.Methods: one hundred healthy males with ages ranging between 20-30 years shared in this study. Three consecutive measures of bilateral shoulder flexion, abduction, internal and external rotation range of motion were performed by the same examiner on each subject by each of the laser and electro-goniometer, with standardized measurement procedures, subjects’ positions, and stabilizations.Results: Pearson (r), paired T-test, and intra-class (ICC) correlation coefficients were used to test the validity and intra-rater reliability of the laser goniometer in comparison to the electro-goniometer. And the results of the validity testing showed a very strong relationship between readings by both devices (r=0.84 to 0.93) and also no significant differences between means of readings of both devices with the p-value ranging between 0.13 and 0.97. Also, ICC revealed high intra-rater reliability of laser goniometer on repeated measures of shoulder range of motions (ICC=0.98-0.99).Conclusion: laser goniometer can be used as a new valid, reliable digital objective method of measurement of shoulder range of motion.